Cofactor-specific covalent anchoring of cytochrome b562 on a single-walled carbon nanotube by click chemistry. Issue 70 (11th July 2016) - Onoda, Akira; Inoue, Nozomu; Campidelli, Stéphane; Hayashi, Takashi
Abstract : Redox-active cytochrome b 562 with a tethered azide group on the heme propionate side chain is covalently linked to an acetylene moiety introduced on the sidewall of a single-walled carbon nanotube by copper-catalyzed click chemistry. Abstract : Redox-active cytochrome b 562 with a tethered azide group on the heme propionate side chain is covalently linked to an acetylene moiety introduced on the sidewall of a single-walled carbon nanotube (SWNT) by copper-catalyzed click chemistry forming a triazole ring with the heme active site directly linked to the SWNT. The cytochrome b 562 –SWNT hybrid is characterized by electrochemistry and atomic force microscopy.